Predicting emotional divorce based on metacognitive beliefs and psychological flexibility - Parvaz, Younes; Bakhtiari, Maryam; Masjedi Arani, Abbas; Asle Zaker, Maryam (Researcher Bulletin of Medical Sciences, 2020)
Introduction: This study aimed to predict emotional divorce based on metacognitive beliefs and psychological flexibility. Materials and Methods: The type of study was cross-sectional. The target population was the total married individuals in Tehran. Using cluster random sampling 467 married people (282 women, 185 man) were chosen to complete the Gottman emotional divorce scale, Meta Cognition Questionnaire (MCQ-30), acceptance and commitment inventory and demographic information sheet. Results: findings showed that metacognitive beliefs and psychological flexibility had a significant relationship (p <0.01) with emotional divorce. These variables accounted for 24% of variance in emotional divorce. Negative metacognitions had a positive significant relationship with emotional divorce. In other words, by incremental level of negative metacognitions the rate of emotional divorce will increase. Also, positive metacognitions and psychological flexibility had a negative significant relationship with emotional divorce. Results showed that by increasing in level of psychological flexibility and applying Positive metacognitions instead of negative metacognitions the rate of emotional divorce will diminish. Conclusion: The current study support empirical evidence that a significant relationship does exist between aforementioned constructs. Given the implications of this research, by modifying of metacognitive beliefs and increasing psychological flexibility, the marital relationship can be improved. Thereby diminishing emotional divorce in couples.